Pengembangan Modul Mengonversi Teks Cerita Rakyat Menjadi Teks Fantasi untuk Siswa - Sukiman (IBTIDA', 2021)
Teaching material is the most important part in the world of education. Because of thist research aims to develop teaching materials that can be used as a source of learning in schools. Teaching material developed in the form of modules converts folklore texts into fantasy texts. This module is used as a companion for teachers in delivering fantasy text and folklore material. The module that was developed has been through the validation test and effectiveness test. Based on the results of the validation test on the feasibility of graphics, the feasibility of the material, the feasibility of the language, and the feasibility of the overall presentation can be implemented. While the effectiveness test results show there is a significant increase in student learning outcomes.